KAJIAN LINGKUNGAN HIDUP STRATEGIS KAWASAN PERUNTUKAN PERTAMBANGAN DI KABUPATEN BOLAANG MONGONDOW - Liza ., Tunggali; Wiske ., Rotinsulu; Zetly ., Tamod (AGRI-SOSIOEKONOMI, 2016)
This qualitative study was analyzed using semi-detailed method is based on the assessment of data and information that is more accurate, can be quantitative. Primary data was collected through interviews with the stakeholders starting from the government officials, the academics and community leaders to get information about important issues emerging in Bolaang Mongondow. Secondary data collected from various government agencies and institutions or personnel associated with the research. The results showed that the mining activities in BolaangMongondow both for exploration and exploitation cause negative impacts by 50%. Starting from the conversion of land that have growing increasingly by time which can certainly bring problems in the future. The implication of uncontrolled agricultural land conversion can threaten food supply capacity and even in the long term can cause social harm. The mining activities, plantation and cultivation will lead to fragmentation of forest landscapes. Forest fragmentation will cause the forest to be smaller in which to live for animals and resulted in less food available for wildlife. There are 6 rivers in Bolaang Mongondow indicated that some parameters that are already above the value of standard quality. They are River Toraut located in the Sub-district of West Dumoga, Totabuan River, Tombolango River located in the Lolak Sub-district, upstream and downstream sections of Wineru River and Nonapan River located in Poigar Sub-District. In addition, natural disasters often occur in Bolaang Mongondow including floods and landslides. This natural disaster resulted in tremendous losses for the community. This study concludes that need to enactment of Regions to regulate mining activities in the area. And also there are should be intensive supervision from the institution concerned. The most important thing is also necessary accomplishment of an alternative control strategies are based on community participation.